Influence of Performance Appraisal on Employee Performance in the Energy Sector Kenya - Mose, Justice; Gachanja, Isaac (PT. Riset Press International, 2024)
Abstract The study focused more on exploring performance appraisal regarding employee performance to ascertain the influence of performance evaluation on employee performance in the energy sector. Similarly the objective of this research was to look into the result of goal setting on employee performance, to find out how career plans influence on workers’ effectiveness, and for determining the extent to which competency-based evaluation influence employees performance, to investigate the impact of ongoing feedback through employee achievement and to assess how incentives affect employee performance in Kenya energy sector through a research paper survey of Kenya Power Ltd. (KP), Kenya Electricity Transmission Company Ltd. (KETRACO), and Kenya Electricity Generating Company PLC. (KenGen), all of which are located in Nairobi County. The researcher used explanatory sequential design method. The study's population was 8820 employees, 11% of total population utilizing a sample size of 801 participant attracted as for all divisions in and to organizations, varying from Senior, middle, and lower-level management employees. Consequently, the researcher used a random sampling technique to collect data from respondents at various levels of management in Kenya's energy sector. Semi-structured questionnaires were used to gather primary data because they allow for open-ended responses from respondents and allow the researcher to easily prepare questions ahead of time to guide the discussion and keep the participants on topic. The collected data was analyzed by use of descriptive statistics and the Statistical Package for Social Sciences (SPSS). Finally, the data was interpreted into measures of central tendency, statistical dispersion, percentages, and person correlations utilizing the frequency distribution. Results were shown in tables, bar charts, and graphs will be used for information presentations. In relation to the impact on employee performance of performance appraisal, the observations suggest that the assessment leads to enhanced productivity in an organization. An effective evaluation model can increase the employees' interest and performance to achieve the specific objectives of the organization. Regarding the influence performance feedback on employee service delivery, the findings showed that effective feedback is crucial to employees to achieve their set objectives. Feedback allows employees to know exactly what is expected of them. The key to the successful empowerment and productivity is effective performance feedback between employees and supervisors. Adequate feedback builds accountability, as staff and supervisors contribute to development goals, skills identification, career development and motivation of employees for enhanced performance. The study concluded that efficient performance appraisal practices allow employees to express their performance challenges, ideas in achieving individual and company's set objectives. Effective feedback on measuring performance can result in improved productivity of employees. In order to improve employee performance, the study recommends optimizing practices for performance management. The contribution of each employee to accomplishing company goals should be the main emphasis of performance reviews.